2002
DOI: 10.1016/s0899-3467(07)60013-5
|View full text |Cite
|
Sign up to set email alerts
|

Cervical curve restoration and forward head posture reduction for the treatment of mechanical thoracic pain using the pettibon corrective and rehabilitative procedures

Abstract: (J Chiropr Med 2002;1:113-115)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…(12)(13)(14)(15)(16)(17)(18) Therefore, symptomatic reduction in the present patient could have originated from multiple sources, including placebo, somatosensory effects from the spinal manipulative procedures, (18) exercise-induced analgesia, (19) or the global realignment of the centers of mass, thus reducing the amount of tension in the postural muscles. (6,20) Patient compliance likely enhanced the results of this program. The home care was performed at a selfreported rate of about 80% of the time, according to the patient.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…(12)(13)(14)(15)(16)(17)(18) Therefore, symptomatic reduction in the present patient could have originated from multiple sources, including placebo, somatosensory effects from the spinal manipulative procedures, (18) exercise-induced analgesia, (19) or the global realignment of the centers of mass, thus reducing the amount of tension in the postural muscles. (6,20) Patient compliance likely enhanced the results of this program. The home care was performed at a selfreported rate of about 80% of the time, according to the patient.…”
Section: Discussionmentioning
confidence: 96%
“…I previously outlined this procedure. (6,7) In conjunction with the anterior headweight, the patient also wore a backpack with 25 pounds of weight over the low shoulder. The weight hangs around the patient's waistline, thereby enhancing the lumbar lordosis immediately.…”
Section: Case Reportmentioning
confidence: 99%
“…There should be little doubt, based on a growing body of evidence (17)(18)(19)(20)(21), that forward head posture and cervical hypolordosis are significant pathologic processes that should be corrected if they are diagnosed. Furthermore, there is a significant amount of research available concerning different methods of correcting these clinical findings (1,2,(22)(23)(24)(25)(26). This provides some evidence that more interdisciplinary health professionals are becoming interested in these structural disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Recent preliminary literature has suggested that the combined use of spinal manipulation and a novel headweight device may correct forward head posture and cervical hypolordosis (1,2). While there is still little evidence to demonstrate the pathognomonic factors resulting in these postural disorders, recent literature has shown the structural and functional consequences of these disease processes (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Specific techniques have been identified that show reasonable effectiveness at restoring cervical lordosis (3)(4)(5)(6)(7). Unfortunately, there is little evidence to show if any techniques can effectively treat cervical hyperlordosis, or if those techniques designed to correct cervical kyphosis or hypolordosis are contraindicated in instances of cervical hyperlordosis.…”
Section: Introductionmentioning
confidence: 99%